Design of a Kinematic Control-Based Motion Control System for Path-Following Robots to Support Sustainable Agriculture - Muhammad Latif; Lusia Permata S. H (Widya Teknik, 2026)
This study focuses on an autonomous robot that can execute plowing motions as a testing medium in agricultural applications is the main goal of this project. The use of line-following robots as the basis for automated systems has been prompted by the quick development of robotics technology. A line-following robot is appropriate for structured field operations since it is made to follow a predetermined course. In order to meet the need for an automated system that can precisely and reliably follow predetermined paths, a line-following robot prototype is developed in this project. The proposed system utilizes a camera as the primary sensor to detect and determine the robot's position in real time. This visual-based approach enables more flexible and adaptive path detection compared to conventional sensors. To control the robot’s motion, a kinematic control method is implemented. This method is selected because it allows precise regulation of both linear velocity and angular velocity, ensuring that the robot can maintain alignment with the path while executing smooth turning maneuvers. Experimental evaluations were conducted on three different field sizes to assess the performance of the system. The results show that the robot achieved an accuracy of 93.49% on a 2 m² field, 94.49% on a 1.5 m² field, and 95.49% on a 1 m² field. These findings indicate that the proposed kinematic control-based system performs effectively in maintaining path-following accuracy across varying field dimensions. In conclusion, the developed robot demonstrates reliable performance as a line-following system and has potential to be further developed for practical agricultural automation applications, particularly in assisting plowing activities with improved efficiency and consistency.